Le doulos [videorecording (DVD)] - Melville, Jean-Pierre, 1917-1973; Melville, Jean-Pierre, 1917-1973; Belmondo, Jean-Paul, 1933-2021-; Reggiani, Serge; Desailly, Jean (KL studio classics., 2019)
The backstabbing criminals in the shadowy underworld of Le Doulos have only one guiding principle: Lie or die. A stone-faced Jean-Paul Belmondo stars as enigmatic gangster Silien, who may or may not be responsible for squealing on Faugel, just released from the slammer and already involved in what should have been a simple heist. By the end of this brutal, twisty, and multilayered policier, who will be left to trust?